Choosing your object of benevolence: a field experiment on donation options - Bodo Aretz; Sebastian Kube (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
In a large natural field experiment, we explore the effect of providing donors with the opportunity to choose the target country for their donations. We find that only a small fraction of donors use the option, which might reflect a reluctance to consider tradeoffs when those concern important, 'protected', values. However, those donors who choose their object of benevolence give significantly more, even when controlling for their donation history. In view of the latest research on identifable-victim effects, our findings underline that less inclusive targets can evoke more intense feelings than more inclusive ones stressing that altruistic motivation seems to be mediated by aroused empathetic emotions.
Keywords: D64; C93; 330; charitable giving; identifiable victim; field experiment; altruism; contingent valuation; Spende; Länderimage; Verhaltensökonomik; Feldforschung; Deutschland